Efficiency Of Irrigation To Meet The Needs Of Rice Fields - Agusri, Erny; Martini, Sri; Aprilyansah, Aji (International Journal of Engineering and Technology, 2023)
Irrigation is an effort to provide and regulate water to support agriculture whose types include surface irrigation, swamp irrigation, underground water irrigation, construction of irrigation canals, so that the availability of water in the Irrigation Area will be fulfilled even though the Irrigation Area is far from surface water sources (rivers). or lake) Planning an irrigation system, the first thing that needs to be done is a hydrological analysis using the Modified Penman method including the water demand in the fields (GFR), the demand for water intake (DR), the clean water requirement in the fields (NFR) as well as the water availability factor which is calculated using FJ Mock method. The hydrological analysis of water demand in the Sumberejo irrigation area aims to determine whether the availability of water is sufficient to irrigate the Sumberejo irrigation area which covers an area of 42.37 Ha. The results of the calculation analysis, it is known that the water requirement for an area of 42.37 Ha, the water discharge in the 1st planting season is 0.16 m3/s, while the water requirement is 0.04 m3/s. the existing water discharge in the 2nd planting season is 0.05 m3/s, while the water requirement is 0.06 m3/s. The determination of the rice-paddy cropping pattern for the first planting season begins in April I and the second planting season begins in August II. Based on the results of the calculation of water needs in the second planting season has not been met.